Effectiveness of ACLS Training Programs: A Comparative Study of Pre- and Post-Test Results Across Health Professional Groups - Fatma Tortum (Sakarya Tıp Dergisi)
Objective: The primary aims of our study were to evaluate the fundamental knowledge and skills related to advanced cardiac life support (ACLS) and basic life support (BLS) across different professional groups through a survey-based assessment and to compare pre-test and post-test surveys following theoretical and simulation-based training to assess improvements in knowledge. Materials and methods: This study was conducted retrospectively between April 1, 2024, and May 15, 2024. The study group consisted entirely of healthcare professionals. The pre-and post-course results of ACLS training provided by 12 emergency medicine specialists with at least five years of experience in ACLS instruction were evaluated. The statistical analyses of the data were performed using the IBM SPSS 25.0 software package. Results: The study included a total of 456 participants, of whom 48.5% (n=221) were male. Among the participants, 35.5% (n=162) were emergency medicine residents. Analysis based on the participants’ roles revealed a statistically significant difference between the pre-test and post-test results (p=0.010). Post-hoc analysis indicated statistically significant differences between general practitioners and nurses, as well as between general practitioners and paramedics (p=0.012 and p=0.029, respectively). Conclusion: The study found that a guided ACLS training program, which included standard didactic, practical, and simulation methods, resulted in improved ACLS and increased ACLS knowledge levels among all healthcare professionals. However, no single professional group exhibited a more pronounced increase in post-course success levels compared to others.